Types of Moral Values in “Ralph Break The Internet Wreck It Ralph 2” - Made Suarjana; Ni Made Verayanti Utami; I Gusti Ayu Vina Widiadnya putri (Journal of Language and Applied Linguistics, 2024)
This study aims to determine the types of Moral Values and the context of the situation when delivering the types of moral values expressed in the film "Ralph Breaks the Internet: Wreck-It Ralph 2. Moral values are discussed using the theory of Types of Moral Values proposed by (Audi, 2007), and the context situation is discussed using the situation context theory proposed by (Halliday & Hasan, 1989). In collecting data, the first step is to watch the film and mark the utterances that contain moral values in each scene and film dialogue. The method used in analyzing the data is a qualitative descriptive method. The writer classified the data based on the type of moral values and then analyzed the context of the situation. The author presented the types of moral values in "Ralph Breaks the Internet: Wreck-It Ralph 2" the film. The author will use screenshots of scenes with subtitles from the film to analyze moral values and utterances or statements related to moral values that are displayed in bold style. Self Confidence, Respect, and Optimism are more dominantly used by characters in this film than other types.